Behaviour and meat quality of Podolian young bulls - Fabio Napolitano; Antonio Girolami; Marcella Spadetta; Giuseppe De Rosa; Ada Braghieri (Italian Journal of Animal Science, 2010)
From April to August 2008, twelve Podolian subjects, aged about 11 months at the beginning of the experimental period, were used to evaluate the effect of rearing system (Confined vs. Freerange) and season (spring vs. summer) on their behaviour and meat quality. Nine sessions of behavioural observations were performed. During a 6-h period, the behaviour of a focal animal, was continuously monitored. In each session a different animal was chosen. All the animals were slaughtered at 18 months of age. Walking (P<0.001) and standing (P<0.05) were lower in summer, whereas inactivity was higher (P<0.05). Free-range bulls spent more time walking (P<0.05), feeding (P<0.001) and standing (P<0.01) and showed a lower number of agonistic (P<0.05) and non-agonistic social interaction than confined animals (P<0.01). Self- and allo-grooming were not affected by rearing system, whereas season influenced self-grooming with higher values in spring (P<0.05). Confined animals showed higher final weights (P<0.05) and a lighter meat (P<0.05), whereas no differences between groups were observed for average daily gains, carcass yield, water holding capacity and a* and b* indexes. Confinement markedly affected the behaviour of the animals, whereas free-ranging had only minor negative effects on meat lightness.